2018
DOI: 10.1039/c8ee01855c
|View full text |Cite
|
Sign up to set email alerts
|

The Achilles' heel of iron-based catalysts during oxygen reduction in an acidic medium

Abstract: Exposing Fe–N–C catalysts to H2O2-byproduct leaves their catalytic sites untouched but decreases the turnover frequency via oxidation of the carbon surface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
383
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(401 citation statements)
references
References 35 publications
16
383
2
Order By: Relevance
“…Based on theoretical and experimental studies, Mayrhofer's group recently reported that FeN x C y moieties in representative Fe‐N‐C catalysts are structurally stable but electrochemically unstable when exposed to hydrogen peroxide (H 2 O 2 ). The reversible surface oxidation of carbon by exposure to H 2 O 2 modulated the electronic properties of Fe, weakening the O 2 ‐binding on the Fe‐based sites and resulting in the performance loss during the PEMFC operation, as shown in the DFT calculation of Figure . These results are supported by a previous study by Mukerjee's group .…”
Section: Comprehending the Durability Of Electrocatalyst By Combiningsupporting
confidence: 82%
See 1 more Smart Citation
“…Based on theoretical and experimental studies, Mayrhofer's group recently reported that FeN x C y moieties in representative Fe‐N‐C catalysts are structurally stable but electrochemically unstable when exposed to hydrogen peroxide (H 2 O 2 ). The reversible surface oxidation of carbon by exposure to H 2 O 2 modulated the electronic properties of Fe, weakening the O 2 ‐binding on the Fe‐based sites and resulting in the performance loss during the PEMFC operation, as shown in the DFT calculation of Figure . These results are supported by a previous study by Mukerjee's group .…”
Section: Comprehending the Durability Of Electrocatalyst By Combiningsupporting
confidence: 82%
“…c) ORR pathways at FeN 4 . Single and double asterisks denote the reaction intermediates adsorbed on the Fe‐center and nearest C‐center, respectively (Reproduced with permission [71]. Copyright 2018, RSC publishing).…”
Section: Comprehending the Durability Of Electrocatalyst By Combiningmentioning
confidence: 99%
“…Since the data shown in Figure 8 are referred to beginning of test conditions, it is important to consider that PEFC fabricated using PGM-free catalysts at the cathode have shown so far important durability issues compared to their Pt-based counterparts. The durability of M-N-C catalysts in PEFC has been documented and discussed by several articles and reviews [88,106,155,162,177,178]. However, as previously stated, it is difficult to compare the performance of the different catalysts at the end of durability test, due to the wide variety of durability protocols that were used in the different works.…”
Section: H 2 /O 2 and H 2 /Air Pefc Performancementioning
confidence: 99%
“… Mild surface oxidation of the carbon material (e.g. by reactive oxygen species (ROS) following the formation of H 2 O 2 by‐product), which hosts the MN x moieties, yielding unmodified SD but decreased TOF values as a result of a modification of the carbon surface properties with increasing content of oxygen functional groups, this type of deactivation being partially reversible upon reduction of the carbon surface. Protonation of highly basic nitrogen groups, followed by anion adsorption, which in ex situ conditions (no electrochemical potential applied), was shown to be also partially reversible, while a fraction of the sites also irreversibly demetallated during acid wash. This phenomenon is particularly important for NH 3 ‐pyrolyzed catalysts or as‐prepared catalysts with highly basic N‐groups. Demetallation of the MN x active sites in acid medium, which has been recently shown to be accelerated when the electrochemical potential is decreased in the ORR range (0.3–0.8 V vs. the reversible hydrogen electrode, RHE) while demetallation is slowed down or insignificant in open circuit potential conditions (0.9–1.0 V vs. RHE). Carbon corrosion and subsequent loss of MN x sites during accelerated stress tests (ASTs) mimicking uncontrolled and transient start/stop (ST/ST) of PEMFCs …”
Section: Introductionmentioning
confidence: 99%